Pengaruh Proporsi Dewan Komisaris Independen, Profitabilitas, Ukuran Perusahaan Terhadap Pengungkapan Corporate Social Responsibility - Muhammad Rizqi Ramadhan; Diah Armeliza; Ati Sumiati (LPPM Universitas Negeri Jakarta, 2025)
This research aims to empirically examine the determinants of Corporate Social Responsibility (CSR) disclosure. Specifically, this study analyzes the influence of governance mechanisms (proportion of independent commissioners), financial performance (profitability), and company characteristics (company size) on the level of CSR transparency. Using a quantitative approach, this study analyzes panel data from 43 energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period (a total of 129 observations). Secondary data were collected from annual reports and sustainability reports. The level of CSR disclosure, as the dependent variable, was measured using a 50-item index from SEOJK No. 16/SEOJK.04/2021, and analyzed using a panel data regression model. The results of the F-test (Goodness of Fit) confirmed that the regression model used in this study was fit for further analysis. However, a partial analysis (t-test) yielded nuanced findings, namely that only company size was shown to have a positive and significant effect, confirming that larger companies tend to be more transparent. In contrast, the proportion of independent commissioners and profitability were found to have no significant impact. Therefore, it can be concluded that in the context of the Indonesian energy sector, operational scale is the primary driver of CSR transparency, while the effectiveness of independent board oversight and financial capacity are not proven to be determining factors.